Peran Kepala Sekolah dalam Implementasi Kurikulum Merdeka: Studi Kasus di Sekolah Dasar Islam Al Furqon Rembang - Ali Wahyudi; Rasiman Rasiman; Soedjono Soedjono (Universitas Negeri Malang, 2026)
Abstract: Education is a cornerstone for human resource development, and curriculum transformation is crucial to enhance learning quality. This study examines the role of school principals in implementing the Independent Curriculum (Kurikulum Merdeka) at SD Islam Al Furqon Rembang. A qualitative case study design was used to explore the principals’ managerial functions, including planning, organizing, directing, and controlling. Data were collected through structured interviews, non-participant observation, and document analysis, then analyzed using Miles and Huberman’s interactive model. Findings reveal that the principal plays a strategic role in designing implementation programs based on school needs, establishing curriculum teams, supervising academic activities, facilitating teacher collaboration, and monitoring learning outcomes. These managerial functions are executed systematically, collaboratively, and adaptively, ensuring alignment with the Independent Curriculum and 21st-century learning demands. The study highlights that successful curriculum implementation strongly depends on the principal’s capacity as an instructional leader and change agent. The findings offer practical implications for strengthening professional development of school leaders and teachers and optimizing student-centered, innovative, and contextualized learning, while fostering character development and essential competencies. Keywords: school principal, Independent Curriculum, school management, instructional leadership, primary education Abstrak: Pendidikan merupakan fondasi pengembangan sumber daya manusia, dan transformasi kurikulum menjadi kunci untuk meningkatkan kualitas pembelajaran. Penelitian ini menganalisis peran kepala sekolah dalam implementasi Kurikulum Merdeka di SD Islam Al Furqon Rembang. Penelitian menggunakan desain studi kasus kualitatif untuk mengeksplorasi fungsi manajerial kepala sekolah, meliputi perencanaan, pengorganisasian, pengarahan, dan pengendalian. Data dikumpulkan melalui wawancara terstruktur, observasi nonpartisipan, dan analisis dokumen, kemudian dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa kepala sekolah berperan strategis dalam merancang program implementasi berdasarkan kebutuhan sekolah, membentuk tim kurikulum, melakukan supervisi akademik, memfasilitasi kolaborasi guru, dan memantau hasil pembelajaran. Fungsi manajerial tersebut dijalankan secara sistematis, kolaboratif, dan adaptif, sehingga selaras dengan Kurikulum Merdeka dan tuntutan pembelajaran abad ke-21. Penelitian ini menekankan bahwa keberhasilan implementasi kurikulum sangat bergantung pada kapasitas kepala sekolah sebagai pemimpin instruksional dan agen perubahan. Temuan ini memberikan implikasi praktis untuk penguatan pengembangan profesional kepala sekolah dan guru, serta optimalisasi pembelajaran yang berpusat pada peserta didik, inovatif, kontekstual, sekaligus mendukung pengembangan karakter dan kompetensi esensial. Kata kunci: kepala sekolah, Kurikulum Merdeka, manajemen sekolah, kepemimpinan instruksional, pendidikan dasar